Olaptesed pegol (NOX-A12) with bendamustine and rituximab: a phase IIa study in patients with relapsed/refractory chronic lymphocytic leukemia - Steurer, Michael; Montillo, Marco; Scarfò, Lydia; Mauro, Francesca R.; Andel, Johannes; Wildner, Sophie; Trentin, Livio; Janssens, Ann; Burgstaller, Sonja; Frömming, Anna; Dümmler, Thomas; Riecke, Kai; et al. (Haematologica (Roma), 2019)
Olaptesed pegol (NOX-A12) is a pegylated structured L-oligoribonucleotide that binds and neutralizes CXCL12, a chemokine tightly regulating the life cycle of chronic lymphocytic leukemia cells. The resulting inhibition of CXCR4 and CXCR7 signaling reduces the protective activity of the bone marrow and lymph node microenvironment. CXCL12 inhibition mobilizes chronic lymphocytic leukemia cells into the circulation and prevents their homing into the protective niches. In this phase I/II study, 28 patients with relapsed/refractory chronic lymphocytic leukemia were treated with olaptesed pegol in combination with bendamustine and rituximab. Combination treatment was preceded by single escalating pilot doses of olaptesed pegol in the first ten patients for evaluation of safety and pharmacokinetics. Peak concentrations and systemic exposure of olaptesed pegol were dose-linear; plasma elimination was monophasic with a 53.2 h half-life. A rapid increase in circulating chronic lymphocytic leukemia cells was observed already 1 h after administration of olaptesed pegol and lasted for at least 72 h. Single-agent treatment was well tolerated and no dose-limiting toxicity was observed. The combination regimen yielded an overall response rate of 86%, with 11% of patients achieving a complete response and 75% a partial response. Notably, all ten high-risk patients, including four with a 17p deletion, responded to treatment. The median progression-free survival was 15.4 (95% confidence interval: 12.2, 26.2) months while the median overall survival was not reached with >80% of patients alive after a median follow-up of 28 months. Olaptesed pegol was well tolerated and did not result in additional toxicity when combined with bendamustine and rituximab ( ). Further clinical development of this novel CXCL12 inhibitor is thus warranted.